Identification of mouse Duffy Antigen Receptor for Chemokines (Darc) as a BMD QTL gene - Edderkaoui, Bouchra; Baylink, David J.; Beamer, Wesley G.; Wergedal, Jon E.; Porte, Ryan; Chaudhuri, Asok; Mohan, Subburaman (Genome Research, 2007)
It is now well known that bone mineral density (BMD) variance is determined by both genetic and environmental factors. Accordingly, studies in human and animal models have revealed evidence for the presence of several quantitative trait loci (QTL) that contribute to BMD variations. However, the identification of BMD QTL genes remains a big challenge. In the current study, we focused our efforts to identify the BMD candidate gene in chromosome 1 (Chr 1) QTL that was detected from a cross involving high BMD CAST/EiJ (CAST) and low BMD C57BL/6J (B6) mice. To this end, we have combined several approaches including: (1) fine mapping the BMD QTL in Chr 1 of the B6.CAST F2 female mice using a large number of polymorphic markers; (2) the generation of congenic sublines of mice by repeated backcrossing of CAST with B6 mice and phenotype characterization; (3) expression profiling genes in the QTL region; and (4) SNP analyses to identify the mouse Duffy Antigen Receptor for Chemokines (Darc) as a candidate gene for Chr 1 BMD QTL2. We verified the involvement of the Darc protein in BMD variation by evaluating the skeletal phenotype of Darc-knockout mice and congenic sublines of mice carrying small chromosomal segments from CAST BMD QTL. Based on the findings that Darc-antibody blocked formation of multinucleated osteoclasts in vitro and that Darc from CAST binds chemokines, known to regulate osteoclast formation, with reduced affinity compared with Darc from B6 mice, we conclude that Darc regulates BMD negatively by increasing osteoclast formation, and that the genetic association between Darc gene polymorphism and BMD variations in humans merits investigation.
10.1101/gr.6009507